Embracing the Change: Personal Experience in Academic Unit Transformation - Hazem Said (Academic Chairpersons Conference Proceedings, 2023)
This presentation will cover personal experience and case study on how academic unit heads can embrace change, build an identity for their unit, and lead their faculty and staff in transforming their unit from obscurity to prominence while under budget constraints and limited authority. The session will draw from personal experience establishing an academic unit and transforming it from a small unknown teaching unit to one of the largest teaching and research units on the campus of a research one university. Over ten years, the grassroots transformation included the hiring of 24 new faculty and 20 new staff and sustaining an annual growth rate of 20% in FTE and 19% in head count with overall enrollment in the major growing from 305 in Fall of 2012 to over 2000 in Spring 2023. The grassroots transformation took place without initial budget investment and was sustained through annual budget cuts and through the pandemic.
Keywords: academic unit; leadership; transformation; unit head; change